Reframing Immigrant Resistance : Alliances, Conflicts, and Racialization in Italy. - Cappiali, Teresa (Milton : Taylor & Francis Group, 2019)
This book focuses on the political participation and grassroots mobilization of immigrants and ethnic minorities. Based on extensive data collected in Italy, it investigates what might explain variations in forms of political participation and grassroots mobilization at the local level.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books